'Single mode' tunable optical microcavities - Di, Z; Dolan, P; Jones, H; Hughes, G; Smith, J; IEEE (2012)
We present tunable open-access optical microcavities with mode volumes ∼ λ3 and Q factors ∼ 104. Purcell enhancement of emission from semiconductor nanocrystals into single cavity modes at room temperature is demonstrated. © 2012 OSA.